School leadership practices of Portuguese principals: matching perceptions of principals and teachers - Cabral, Ilídia (2021)
This paper presents a study on teachers' and principals' perceptions of school leadership practices in Portuguese schools. Using the Multifactor Leadership Questionnaire, perceptions about transformational, transactional and laissez-faire leadership practices and its consequences on leadership outcomes (followers' extra-effort, leaders' effectiveness and followers' satisfaction with leader) were collected from representative samples of Portuguese teachers (N = 21,082) and principals (N = 122). Results point to differences in the perceptions on leadership practices between principals and teachers: teachers tended to rate principals lower than the latter rate themselves in all transformational and transactional dimensions of leadership; most teachers did not perceive a dominant leadership style in their principals, whereas most principals see themselves as predominantly transformational. Also, for teachers, leadership practices have a higher impact on leadership outcomes than for principals. These results and their practical implications are discussed in the last sections of the paper.